Coordinated path-following and direct yaw-moment control of autonomous electric vehicles with sideslip angle estimation. (15th May 2018) - Guo, Jinghua; Luo, Yugong; Li, Keqiang; Dai, Yifan
Highlights: A novel coordinated PFS and DYC control system of autonomous electric vehicles is proposed. The proposed control system can strengthen the lateral stability and improve the path tracking performance. Vehicle sideslip angle is estimated by the data fusion of low-cost GPS and INS. Abstract: This paper presents a novel coordinated path following system (PFS) and direct yaw-moment control (DYC) of autonomous electric vehicles via hierarchical control technique. In the high-level control law design, a new fuzzy factor is introduced based on the magnitude of longitudinal velocity of vehicle, a linear time varying (LTV)-based model predictive controller (MPC) is proposed to acquire the wheel steering angle and external yaw moment. Then, a pseudo inverse (PI) low-level control allocation law is designed to realize the tracking of desired external moment torque and management of the redundant tire actuators. Furthermore, the vehicle sideslip angle is estimated by the data fusion of low-cost GPS and INS, which can be obtained by the integral of modified INS signals with GPS signals as initial value. Finally, the effectiveness of the proposed control system is validated by the simulation and experimental tests.